Wireless multimedia sensor network technology: a survey - Sharif, Atif; Potdar, Vidyasagar; Chang, Elizabeth (IEEE, 2009)
Wireless Multimedia Sensor Networks (WMSNs) is comprised of small embedded video motes capable of extracting the surrounding environmental information, locally processing it and then wirelessly transmitting it to parent node or sink. It is comprised of video sensor, digital signal processing unit and digital radio interface. In this paper we have surveyed existing WMSN hardware and communicationprotocol layer technologies for achieving or fulfilling the objectives of WMSN. We have also listed the various technical challenges posed by this technology while discussing the communication protocol layer technologies. Sensor networking capabilities are urgently required for some of our most important scientific and societal problems like understanding the international carbon budget, monitoring water resources, monitoring vehicle emissions and safeguarding public health. This is a daunting research challenge requiring distributed sensor systems operating in complex environments while providing assurance of reliable and accurate sensing.